Implementation of Community Education and Knowledge Development in the Utilization of Digital Literacy - Poniyah Simanullang; Selli Dosriani Sitopu; Ester Mei Frida Girsang; Fransiskus Gultom (Jurnal Penelitian Pendidikan IPA, 2023)
This research was conducted in the library of the health center at Posyandu (Integrated Service Post) located in Pasar Borbor Village. Research is carried out once a month in the second week with routine activities for the community. Geographically, Posyandu is far from residential areas, difficult for the community to reach, so there has been a decrease in visits from mothers with toddlers. The purpose of this study was to analyze "Implementation of community education and knowledge development in the utilization of digital literacy in the library of the Borbor Sub-District Public Health Center". The research method used is a descriptive qualitative research method. The population in the study were mothers who had 91 children under five, 41 of whom were samples taken using the accidental sampling technique. To obtain data in assessing knowledge and compliance is done by using a data collection instrument in the form of a questionnaire. The data obtained was then analyzed using the Chi Square statistical test with a value of Î± = 0.05. The research results obtained show: 1) the majority of the utilization of digital literacy is Â± 43.9%, and does not utilize digital literacy of 56.1%; 2) Lack of knowledge of mothers under five is the main reason for not utilizing digital literacy when visiting posyandu, 3) There is a relationship between knowledge and utilization of digital literacy during visits (p=0.000), 4). Mothers of toddlers who have good education and knowledge make more use of digital literacy to make visits to posyandu compared to those who have less education and knowledge. The results of the research really hope that the community will take advantage of digital literacy in visiting the nearest Posyandu